The Efficiency of Drip Irrigation and Crop Water Requirement of Cauliflower on Andosol Land - Irvan Immanuel Silalahi; Sumono Sumono; Saipul Bahri Daulay; Edi Susanto (Jurnal Rekayasa Pangan dan Pertanian, 2013)
This research was held to calculate and assess the efficiency of drip irrigation and crop water requirement of cauliflower on andosol land. The parameters observed were the efficiency of the use of water, the efficiency of the water storage and crop water requirement. The results of this experiment indicated that the lowest water consumption efficiency was occurred in the early phase of growth i.e 91,85%, the largest water consumption efficiency was occured in the middle and end phase of the growth i.e 100%. The lowest water storage efficiency was occurred at the early phase of growth ie 23,77%, the largest water storage efficiency was occurred in the final phase i.e 76,42%. Crop water requirement in the initial phase was 2.88 mm.day-1, in the middle phase of growth was 6,58 mm.day-1 and the final phase of the growth was 6.1 mm.day-1. Key words: Efficiency, Drip Irrigation, Crop Water Requirement, Andosol Land, Cauliflower